Therapeutic effects of topical Mycophenolate mofetil on hydroquinone-induced depigmentation in Guinea pigs and mice - Yuan Guo; Yi-fei Yang; Yanhua-Li; Yun Zhang; Haixia-Shi (Annals of Medicine)
Background Vitiligo is a depigmentation disorder with an undefined specific pathogenesis, with the autoimmune theory being a prominent etiology. Mycophenolate mofetil (MMF), a novel immunosuppressant, selectively inhibits inosine 5-monophosphate dehydrogenase (IMPDH), crucial for lymphocyte DNA synthesis. Recent research has highlighted MMF’s efficacy in vitiligo treatment; however, the precise mechanism remains unclear. This study aimed to explore the therapeutic impact and mechanism of vitiligo.Methods We enrolled guinea pigs and C57/BL6 mice which were randomly divided into the hydroquinone group, the MMF & hydroquinone group, and the control group. Skin biopsy specimens were collected from designated areas which were stained using hematoxylin and eosin (H&E), Masson-Fontana (M-F), and immunofluorescence techniques. To elucidate the pharmacological mechanisms underlying the effects of MMF, real-time polymerase chain reaction (PCR) and western blotting analyses were performed.Results A comparative analysis revealed a notable enhanced pigmentation in the MMF-conjunction group. Subsequent to MMF application, there was a significant augmentation in both the number of melanocytes within the basal layer and melanin-containing hair follicles. MMF activated tyrosinase (TYR), which had been suppressed by hydroquinone, and led to an upregulation of melanin-associated genes such as TYR, TYRP-1, MITF, and SILV. Additionally, there was an increase in WNT pathway-related proteins, including β-catenin, GSK3β, Axin2, Dkk, and Dact2. MMF effectively mitigated the vitiligo-like increase in IFN-γ induced by hydroquinone safely.Conclusion MMF exhibits a notable capacity to ameliorate the pigment-loss effect associated with hydroquinone through the activation of the WNT signaling pathway. Consequently, MMF emerges as a promising therapeutic agent for mitigating skin pigmentation.